Microphone array techniques for aeroacoustics - Jordan, Peter (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2001)
The capacity for source localisation and measurement in aeroacoustics can be enhanced through the use of a microphone array. Although arrays have been used in a variety of applications, there are a number of problems manifest in their use for analysis of specific systems. The first of these is the dependence of the response characteristic of an array on the source frequency of the system being analysed. This can lead both to spurious source identification and erroneous source measurement. In this work a technique developed for radio antenna applications is adapted to give additional response control for linear arrays with commensurate element spacing. This is then applied to an aeroacoustic system consisting of twin high-speed propellers where the noise generated by one propeller is to measured, while contributions from the other are filtered out. The second problem arises due to aeroacoustic source directivity. This problem is illustrated by means of a simple model, which shows that erroneous results are obtained when a dipole source is measured using an ordinary beamformer. A procedure which allows the location and orientation of such a source to be identified is proposed, and a correction applied to the beamformer such that it correctly measures the source. This procedure is then applied to an experimental aeroacoustic system containing a single dipole in the form of a cylinder in cross-flow. A general methodology for aeroacoustic analysis based on these developments is proposed and its implementation discussed.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin